Investment Profile of Working Women in Pakistan: A Case Study - Unais, Shahana (JISR management and social sciences & economics, 2009)
Research on gender poverty accentuates that the earning gap that occurs due to gender gap and mother gap is mainly responsible for poverty among elderly women. Besides, women’s low preference for their own old age needs, high importance attached to family needs and low risk taking capacity reduces savings. This paper explores the savings and investment profile of working women in urban Lahore, Pakistan to determine whether earning gap is the main cause of low savings and investment or not. Data has been collected through a selfconstructed survey of 300 working women on saving and investment related quantitative and demographic variables. The main finding of this research is that women, regardless of their marital status, attach highest importance to family needs.